NILAI MORAL DALAM LIRIK DOLANAN CUBLAK-CUBLAK SUWENG - Ariesta, Freddy Widya (JURNAL ILMU BUDAYA, 2019)
This article aims to examine the moral values contained in the lyrics of dolanan cublak-cublak suwengIn terms of the cultural dolanan song contains many meanings that can provide moral teachings to the children in order to discipline, maintaining harmony with nature, fellow human beings, and parents. Methods of data collection using the literature study on understanding the lyrics, lyric history, the meaning of the lyrics and the lyrics dolanan moral values Cublak-Cublak Suweng. The lyrics of the song on dolanan cublak-cublak suweng have a broad range of activities and behaviors and have a variety of objectives towards the moral values contained therein which are full of meaning and good philosophical basis. So the results of the analysis of the moral messages contained in the lyrics Cublak-Cublak Suweng can be useful for the development of character and cultivation of moral values in children from an early age, especially at the elementary school age